气体发动机的进气管总成 (2018)
本发明公开了种气体发动机的进气管总成，包括：进气歧管，其由若干两缸段型接管连接而成，该进气歧管的两端的管口均设有端盖，处于该进气歧管的中间位置的两缸段型接管的侧壁上设有法兰型接口；以及进气管，进气管包括：第弯管，其与法兰型接口连接，第弯管的弯壁外侧上设有防爆阀；第段接管，该第段接管与第弯管连接，第段接管与第弯管之间接有进气阻火器；以及第二段接管，该第二段接管与第段接管连接，第二段接管和第段接管与进气歧管平行，第段接管与第二段接管之间接有电子节气门，第二段接管的末端连接有进气接管。该进气管总成可以为气体发动机安全提供燃料。 The invention discloses an air inlet pipe assembly of a gas engine. The air inlet pipe assembly of the gas engine comprises an air inlet branch pipe and an air inlet pipe; the air inlet branch pipe is formed by connecting multiple two-cylinder-one-section type connecting pipes, pipe openings of the two ends of the air inlet branch pipe are both provided with end covers, and the side walls of the two-cylinder-one-section type connecting pipes which are located in the middle of the air inlet branch pipe are provided with flange type connectors; the air inlet pipe comprises a first bent pipe, a first section connecting pipe and a second connecting pipe, wherein the first bent pipe is connected to the flange type connectors, and an anti-explosion valve i